Characteristics of blood infections and phenotypic detection of extended-spectrum β-lactamases in ICU patients in Central India posing a challenge - Trivedi, Moha S.; Nagendra, Manish (International Journal of Research in Medical Sciences, 2023)
Background: Bloodstream infection (BSI) is defined by positive blood cultures in a patient with systemic signs of infection and may be either secondary to a documented source or primary, that is, without identified origin. The aim of this study was to improvise blood culture systems for a quicker, optimum diagnosis and prompt treatment. Methods: A prospective study was conducted with total of 309 samples for determining the bacteriological profile and prevalence of ESBL in BSI’s in patients admitted in the ICU’s (surgical/medical/gynaecological) with the suspicion of sepsis. Samples received in department of microbiology were processed as per standard protocol and identification of bacteria was carried out with the help of relevant biochemical tests. AST for both the ICUs was done together by Kirby-Bauer disk diffusion method according to CLSI guidelines. Results: Of the total, 149 (48.22%) samples were positive for growth with the major isolates out of these being gram negative bacilli, 104 (69.79%) and 45 (30.21%) were gram positive cocci. Among the gram negative bacilli, Klebsiella pneumoniae 35 (33.65%) was the most common bacteria while the least frequent organism isolated was Acinetobacter baumanii 10 (9.62%). Imipenem, piperacillin-tazobactam and levofloxacin were the most sensitive antibiotics whereas cefepime, cefuroxime were the most resistant antibiotics. Conclusions: This study highlights the incidence of gram negative bacilli in ICU’s and the emergence of multi-drug resistant organism. Infections with MDR organisms can lead to inadequate or delayed treatment which is associated with adverse patient outcomes.